Cajal bodies and snRNPs - friends with benefits. Issue 6 (3rd June 2017) - Staněk, David
ABSTRACT: Spliceosomal snRNPs are complex particles that proceed through a fascinating maturation pathway. Several steps of this pathway are closely linked to nuclear non-membrane structures called Cajal bodies. In this review, I summarize the last 20 y of research in this field. I primarily focus on snRNP biogenesis, specifically on the steps that involve Cajal bodies. I also evaluate the contribution of the Cajal body in snRNP quality control and discuss the role of snRNPs in Cajal body formation.